Epilepsy and seizures in children with congenital heart disease: A prospective study. (January 2019) - Desnous, Beatrice; Lenoir, Marien; Doussau, Amélie; Marandyuk, Bohdana; Beaulieu-Genest, Laurence; Poirier, Nancy; Carmant, Lionel; Birca, Ala; ,
Abstract: Purpose: Children with complex congenital heart disease (CHD) experience high incidence of perioperative seizures. Population-based studies also report high epilepsy co-morbidity in CHD. Given the increasing survival of patients with CHD and the interference of seizures and epilepsy with the long-term outcomes, characterizing them in this population is of high relevance. This study investigated the incidence and risk factors of perioperative clinical seizures (CS) and epilepsy in a prospective cohort of children with complex CHD who underwent cardiac surgery. Methods: We included 128 consecutive children with CHD, followed for at least two years at the neurocardiac clinic of Montreal's Sainte-Justine University Hospital Center. We collected perinatal, surgical, critical care and clinical follow-up information and performed logistic regression to reveal risk factors of CS and epilepsy. Results: Ten patients (7.8%) experienced perioperative CS. Four of them (40%) developed epilepsy. The incidence of epilepsy was therefore 3.1%. Higher surgical complexity scores, delayed sternal closure, extracorporeal membrane oxygenation (ECMO) use, longer intensive care and hospital stay were associated with CS. ECMO use and hospital stay were also associated with epilepsy. Nine (90%) patients with CS had brain injuries: five strokes, one white matter and three hypoxic-ischemic injury (HII). All patients with HII developed epilepsy, which became intractable in one of them. Conclusion: Our study reports high incidence, surgical risk factors and brain injury patterns underlying CS and epilepsy in CHD. Further studies are needed to investigate how epilepsy interferes with neurodevelopment and quality of life in CHD.